Impact of the hematocrit value of the blood prime unit on patient hematocrit values after therapeutic plasma exchange in children weighing 10 kg or less. Issue 4 (28th December 2018) - Aldarweesh, Fatima; Schaser, Karen; Weiss, John; Connor, Joseph
Abstract : We report the impact of measuring the hematocrit (HCT) of blood prime units (BPUs) on postprocedure patient HCT values in a small child with transverse myelitis undergoing therapeutic plasma exchange (TPE). Initially, the BPU HCT values were not measured, according to our apheresis policy of using our blood center's estimated HCT value. This approach resulted in unexpected increasing elevations of our patient's post‐TPE HCT after the first two TPE procedures. Subsequent measurement of the BPU HCT prior to use stabilized the patient's post‐TPE HCT. To our knowledge, this is the first case report describing the impact of using the measured BPU HCT vs the estimated HCT for very small children undergoing therapeutic apheresis. Our standard operating procedure for very small children has been updated after this patient's case to include measurements of the HCT values of BPUs for children who weigh 10 kg or less.